Plagas que atacan la plantula - Schoonhoven, Aart van (United Nations Development Programme, 1985)
The following insect pests attacking bean seedlings are briefly described and the damage they cause is mentioned: Delia platura, Gryllus spp., Phyllophaga spp., Elasmopalpus lignosellus, Slugs, and cutworms. Some cultural and chemical control measures are indicated. (CIAT)